Pemanfaatan Greenhouse Sekolah Sebagai Sumber Belajar Pada Muatan Pelajaran IPA Sekolah Dasar - Issaura Sherly Pamela; Fajar Prasetiawan (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The purpose of this study is to describe the use of the greenhouse school environment as a learning resource in the content of elementary school science lessons. This research is qualitative research with the type of phenomenology. The instruments used in this study, namely: observation, interviews, and documentation. The informants who were interviewed in this study were principals, teachers, and students. The results of this study indicate that planning for the use of the greenhouse as a learning resource, namely, preparing lesson plans, preparing tools/materials, preparing learning resources (teacher thematic books, student thematic books, and additional greenhouse learning resources), preparing observation sheets, paper for making reports. and pen. Implementation activities consist of preliminary activities, core activities, and closing activities. One of the lesson content that utilizes the greenhouse as a learning resource is the content of science lessons where students learn the material for plant parts and their functions and learn the characteristics of maintained and untreated plants. Evaluation activities are carried out by the teacher by evaluating related to planning and implementation in learning.